The Relationship Between Construction Workers’ Perception of Accidents and Risk Management - Vallejo Romo, Lucila del Carmen (2025)
Occupational accidents often result from inadequate implementation of preventive measures designed to ensure a safe work environment. Research into accidents often overlooks workers’ perspectives, leading to solutions that solely reflect the company’s perspective. By incorporating workers’ perceptions, a new approach to accident prevention can be developed to optimize risk management and introduce innovative prevention strategies. This research study aimed to determine the relationship between workers’ perceptions of accidents and risk management within a construction company. A non-experimental quantitative approach was used and surveys were employed to gather accurate data. The study tested the direct relationship between construction workers’ perception of accidents and the company’s risk management strategies.